Рента как экономическая категория - Голубцова, А. В. (БНТУ, 2023)
In this work, the concept of rent in economic theory is considered. Historically, rent has been associated with payment for the use of natural resources, especially land. However, in modern times, rent includes other types of resources. Depending on the type of resource, various types of rent are allocated, such as administrative, water, mining, political, and others. Rent may arise due to monopoly control over the resource. Types of rent and their mechanisms depend on the level of development of productive forces and industrial relations in society.